Chinese Ghost Story - Boord, Dan; Valdovino, Luis (United States : Boord, Dan ; Valdovino, Luis, 2008)
A film essay in which history and landscape converge to explore the construction of the 1869 Transcontinental Railroad, where 1300 Chinese laborers lost their lives. While the remains of many were eventually shipped home, others lie in unmarked graves throughout the American West.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films